Immunological Changes Associated with Rheumatoid Arthritis - Mohammed Abd Jwad (Journal of Global Pharma Technology, 2018)
Rheumatoid factors (RF) are IgM autoantibody directed against the Fc portion of IgG. Rheumatoid factor is a well-established distinguishing and prognostic test in Rheumatoid Arthritis. High titer IgM RF is relatively specific for the RA diagnosis in the context of chronic poly arthritis, and was for decades the sole serologic criterion widely used in diagnosis of RA. Those, whom likely to assume a more prompt destructive form of disease in particular, are subject to early identification, It is vital to because the benefits gained in laying early aggressive mediation with disease modifying agents. A variable disease course is to be followed by patients where outcome measures are to be calculated such as functional status and radiological assessment of joint damage. An increasing risk is manifested for those patients with an established RA diagnosis. Positive testing results, anti-CCP antibodies or both are placed in a category of developing an erosive joint damage and impairment of function. As a result, patients should receive an anti-rheumatic therapy that could suppress the disease early stage activity. Patients, who are RA and anti-CCP diagnosis both be considered. Rheumatic factors are the conspicuous markers for patients with RA. Those markers are useful clinically .Antibody Rheumatic factors and anti-CCP testing is necessary for predicting and diagnosing of functional and radiographic outcomes. Patients with early diagnosed arthritis and who are anti-CCP and RA antibody positive considered being at higher and increasing risk of manifesting development of erosive joint disease. While those patients with neither markers are less likely to be develop the like symptoms, thus, symptomatic treatment (e.g. with non-steroidal anti-inflammatory drugs) may be appropriate for those lacking both anti-CCP and antibodies RF. From June 29th to October 1st (2016) this research was conducted during the mentioned period at Baghdad teaching hospital consultation clinic, which involved (47)patients with RA, they were 13 male and 32 female , this data was then subjected to statistical assessment by the IBM SPSS program 20th version which comprised of the arithmetic mean, Standard deviation, SEM, the study is aiming to identify the factor of rheumatoid in the diagnosis of RA and the value of biologic markers that have been assessed for disease activity assessment and for the prognosis of rheumatoid arthritis, particularly the use of anti-CCP antibodies test in diagnosis and predicting the prognosis of rheumatoid arthritis.Keywords: Predictive and prognostic values of Rheumatoid factor, Rheumatoid factor Titer, anti-CCP antibodies.